(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background - Osteoarthritis of knee being of the major causes for disability in older population. Due to sedentary lifestyle this disease is becoming common in younger population as well. As prevalence of the disease is increasing it is a need of the hour to come up with a highly reliable exercise protocol which will be beneficial for the patients. This research aims to establish a beneficial and reliable exercise protocol which can be well tolerated by the patients suffering from osteoarthritis of knee. Methods – 150 subjects will be selected. Randomly they will be assigned to two groups that is Group A and Group B using chit method. Group A will receive Blood Flow Restriction Training and Group B will receive retro walking training. Training will continue for 15 days. After 15 days patient will be reassessed for pain, strength and WOMAC score. Result – Studies have proved that Blood Flow Restriction Therapy and retro walking both the intervention are beneficial in patients of osteoarthritis to reduce pain, improve strength and WOMAC score. This study will provide us an intervention which is beneficial in treating osteoarthritis and is well tolerated by the patients. We may get a result where blood flow restriction would have a better impact on few outcome measures while retro walking may fetch better impact on other outcome measures. We may also conclude that combination of both the interventions is a better option for the treatment of osteoarthritis patients.